2001
DOI: 10.1074/jbc.m101851200
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S Regulates the Expression of Cathepsin L and the Turnover of γ-Interferon-inducible Lysosomal Thiol Reductase in B Lymphocytes

Abstract: Loading of antigenic peptide fragments on major histocompatibility complex class II molecules is essential for generation of CD4؉ T cell responses and occurs after cathepsin-mediated degradation of the invariant chain chaperone molecule. Cathepsins are expressed differentially in antigen presenting cells, and mice deficient in cathepsin S or cathepsin L exhibit severely impaired antigen presentation in peripheral lymphoid organs and the thymus, respectively. To determine whether these defects are due solely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 50 publications
6
33
0
Order By: Relevance
“…In the absence of this chaperone, mature cathepsin L is degraded with faster kinetics (73). Moreover, the double-chain form of cathepsin L in some antigen-presenting cells is inactive (74), similar to that observed for cathepsin B in the studies reported here. Thus, the inhibition of cathepsin B and the cathepsin B-sequestration complex in LX cells may function in a manner analogous to the cathepsin L inhibitor p41 in antigen-presenting cells.…”
Section: Discussionsupporting
confidence: 61%
“…In the absence of this chaperone, mature cathepsin L is degraded with faster kinetics (73). Moreover, the double-chain form of cathepsin L in some antigen-presenting cells is inactive (74), similar to that observed for cathepsin B in the studies reported here. Thus, the inhibition of cathepsin B and the cathepsin B-sequestration complex in LX cells may function in a manner analogous to the cathepsin L inhibitor p41 in antigen-presenting cells.…”
Section: Discussionsupporting
confidence: 61%
“…Alternatively, this disparity may be the result of the differential expression of cysteine cathepsins between these APCs. Although cathepsin L mRNA and protein is detectable in DCs, cathepsin L activity is notably absent (43,57,58). Macrophages, alternatively, express high levels of the active form of cathepsin L (4,41).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this, T cell hybridomas were first stably transfected with an NFA-T-enhanced IL-2 promoter-driven eGFP construct, followed by multiple rounds of selection by FACS to enrich those hybridoma clones that expressed eGFP only following presentation of their cognate peptide epitope by APCs (25). When added to BMMfs that were previously pulsed with HEL protein, we found that WT and Cybb 2/2 BMMfs were equally able to induce eGFP expression in two of the hybridomas (Hb1.9 and H46.13), indicating that the processing/presentation efficiency of HEL [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and HEL [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] peptides were unaffected by NOX2 (Fig. 2D).…”
Section: Nox2 Activity Influences Mhc-ii Presentation In An Ag-specifmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Priess lysates contained only background levels of CatB activity toward the substrate Z-Arg-Arg-AMC, but reacted considerably with the substrate Z-Phe-Arg-AMC, which is cleaved by both CatB and CatL. Primary human B cells and EBV-transformed B cell lines are known to contain active CatS and CatB, but apparently they lack CatL activity (7,32,34,35). Priess cells contained 41 kDa pro-CatL and the 29/34 kDa form of mature CatL, which were not detectable in MGAR cells (Fig.…”
Section: Variability In Lysosomal Enzyme Activity Among Ebv-transformmentioning
confidence: 99%